The Europeanization of Dutch National Spatial Planning: an Uphill Battle. - Zonneveld, Wil (TH Zürich, ORL-Institut, 2005)
So wie die Niederlande von Anfang an Teil des europäischen Integrationsprozesses waren und aufgrund ihrer Lage den "natürlichen" Zugang nach Nordwesteuropa bildeten, so bedeutsam war auch die Rolle der niederländischen Raumplanung in der Formulierung der Agenda einer gemeinsamen europäischen Raumentwicklung. Lokale und Regionale Verwaltungseinheiten beteiligen sich an zahlreichen grenzübergreifenden und transnationalen Kooperationen in der Raumplanung. So könnte man erwarten, dass die niederländische Raumplanung eine starke europaweite Perspektive aufweisen würde. Das ist nicht der Fall. Der Beitrag zeigt, in welchem Maße die niederländische Raumplanung von wechselnden Entwicklungen auf europäischer Ebene abhängt. Er versucht zu erklären, wieso sie sich immer wieder auf die lokale Ebene der Großstädte zurückzieht und dabei u.a. an der Doktrin des Stadt-Land-Gegensatzes und der Bewahrung eines "grünen Herzens" des Landes orientiert ist. oc/difu

The Netherlands has been part of the European integration process from the early days. It has an open economy and has benefited greatly from being a "natural" entrance to North-West Europe. It should not come as a surprise that Dutch spatial planners, mostly officials of the National Spatial Planning Agency, have played a major role during the past decades in discussions on a European planning agenda. They contributed greatly to the making of the European Spatial Development Perspective. Local and regional governments are enthusiastically participating in the various EU programmes on cross-border and transnational cooperation in the field of spatial planning. But how does this relate to domestic spatial planning policies? The country is maintaining one of the most elaborate and sophisticated systems of national spatial planning and policy. One would expect, knowing the participation in European policy programs and discussions on territorial governance, that Dutch national spatial planning policies do have a strong European inclination. This is not the case though. The paper examines to what extent Dutch national spatial planning is influenced by changes at the international level, especially on the European scale. It also seeks to explain why Dutch national spatial planning is constantly returning to domestic planning issues, mainly on urban form, which play themselves out at lower scales than the national. difu
Keywords: Raumordnung; Raumordnungspolitik; Raumplanung; Raumstruktur; Planungstheorie; Planungsgeschichte; Planungswissenschaft